EFFECT OF QUALITY SERVICE, PRICE AND STORE ATMOSPHERE ON CUSTOMER SATISFACTION (STUDY ON CANGKIR COFFEE SHOP IN SURABAYA) - effendy, faries hizrian (Ekspektra : Jurnal Bisnis dan Manajemen, 2019)
This is study aimed to investigate the effect of service quality, price and store atmosphere on customer satisfaction. The research object was Cangkir Coffee in Surabaya. The population of this study were customer of cangkir Coffee Surabaya. The sampling technique was incidental sampling technique; thus the samples were 100 customers who were unintentionally met at Cangkir Coffee Surabaya. Moreover, the analysis technique for this research data applied multiple regression models.The result of classic assumption test that were obtained from normality, multicollinearity and heteroscedasticity indicated that all variables did not contravene the specified condition. While, the result of feasibility test, the regression model that was utilized in this study was feasible. As the result of multiple determination coefficient, the variables of sevice quality, price, and store atmosphere were about 58.8%, indicating the customer satisfaction variable. Furthemore, the partial test result found that the service quality, price and store atmosphere variables had significant and positive effects on customer satisfaction.